Initial Test of the Feasibility and Social Validity of a Transdiagnostic Cognitive Behavioral Intervention with Children with, or At-Risk for, Disabilities - Mickey Losinski; Sara A Sanders; Ashley J Shaw (Bilişsel Davranışçı Psikoterapi ve Araştırmalar Dergisi)
This study sought to determine the feasibility and social validity (acceptability) of a new cognitive behavioral intervention (CARE) for students in the upper elementary grades. Results of the study showed the program to be both feasible and acceptable by school stakeholders. Overall, the program seemed to be more acceptable to teachers and students in the 5th and 6th grades compared to those in the 3rd and 4th grades. Student outcomes were varied, with 3 of the 5 students experiencing visually compelling reductions in problem behaviors, while the other two maintained their baseline problem behaviors. In the following we will discuss the results with respect to the research questions and provide limitations and future directions for research. [JCBPR 2019; 8(2.000): 87-93]